Hak Khiyar Dalam Perlindungan Konsumen Menurut Mazhab Syafi’i Dan Hukum Positif (Studi Kasus Jual Beli Buku Bersegel di Toko Buku Pustaka 2000 Kecamatan Lubuk Pakam) - Leni Masnidar Nasution (Al-Fikru)
Among muamalah activities is buying and selling. Today the practice of buying and selling is growing apart from all kinds of things one of them is a book. Nowadays, the sale of books is packaged with plastic seals so that it attracts buyers. One of these books was sold at the Bookstore Pustaka 2000 in Lubuk Pakam District. The practice of buying and selling is bizarre for some consumers / buyers. When further investigated, the vulnerability of neglected consumer rights makes the pattern of buying and selling in the shop contradict with Islamic law and Positive Law. This research is a field research with a qualitative approach using analytic descriptive method, the implication of  which is by describing the author's analyzes of phenomena that occur in the midst of society within the object of research based on Islamic normative theory, especially according to the perspective Syafi'i school and Positive Law.